The Role of Exchange Rate As a Moderating Variable in CAR, NPF and BOPO Influencing Profitability - Desman Serius Nazara; Dede Hertina; Listiana Sri Mulatsih; Alfiana; Loso Judijanto (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: A bank's capacity to generate earnings on the goods produced by its daily operations is a crucial sign of its financial health. With the exchange rate serving as a moderating element.Purpose: The objective of this study is to ascertain how operating costs, CAR, NPF, and BOPO affect ROA. Design/methodology/approach: Regression analysis is one of the quantitative methods used in the research process. As an illustration, take into account Islamic Commercial Banks that routinely release their financial reports for the years 2018–2022 and are listed on the Indonesia Stock Exchange. 35 samples from 7 different organizations were collected for this study using the purposeful sampling technique. The data was analyzed using partial least squares-structural equation modeling (PLS-SEM). Findings/Result: The exchange rate, BOPO, and NPF all have a major effect on ROA. Meanwhile, the CAR has little effect on ROA in Islamic Commercial Banks between 2018 and 2022. The impact of exchange rates on ROA can be lessened for BOPO and NPF, but not for CAR, as the latter has no control over ROAConclusion: The study's conclusions demonstrate that the exchange rate, BOPO, and NPF all have a major effect on ROA. Meanwhile, the CAR has little effect on ROA in Islamic Commercial Banks between 2018 and 2022. The impact of exchange rates on ROA can be lessened for BOPO and NPF, but not for CAR, as the latter has no control over ROA. The establishment of an efficient capital adequacy ratio for Islamic banking is facilitated by this research, which enhances financial performance.Originality/value (State of the art): The originality/value (State of the art) of this research is by providing empirical evidence about the importance of risk management and operational efficiency in determining the financial performance of Sharia Commercial Banks. On the other hand, this research also highlights that although capital is important, operational factors and credit risk are more dominant in influencing ROA. Keywords: CAR, BOPO, NPF, ROA, Islamic Commercial Banks